Induction of volatile organic compounds in Triticum aestivum (wheat) plants following infection by different Rhizoctonia pathogens is species specific. (June 2022) - Piesik, Dariusz; Lemańczyk, Grzegorz; Bocianowski, Jan; Buszewski, Bogusław; Vidal, Stefan; Mayhew, Chris A.
Abstract: The most popular means of plant protection is the chemical method, but this control is often connected with the need for repeating chemical treatments. Thus, eco-friendly strategies should be developed where, under the European Green Deal, aromatic plants and their repellent properties seem to constitute a good alternative. In earlier studies, we have shown that insect injury, bacteria infestation and pathogen infection induce plant volatile organic compounds (VOCs) emission, which can provide defensive functions to plants. In this study, Triticum aestivum L. (Poaceae) cv. 'Jenga' wheat plants were intentionally infected with one of four Rhizoctonia species ( R. cerealis, R. solani, R. zeae, and R. oryzae ). The soil was inoculated by the pathogens during sowing, whereas shoots were inoculated at stage BBCH 33. In greenhouse experiments, we measured VOCs from wheat 3, 7 and 11 days following stem infestation, or 42 days following soil inoculation of Rhizoctonia spp. VOC emissions were found to be largest on days 7 or 11 post-stem inoculation (>3 days post-stem inoculation >42 days post-soil inoculation). T. aestivum infected by pathogens induced five common green leaf volatiles (GLVs), namely (Z)-3-hexenal = (Z)-3-HAL, (E)-2-hexenal = (E)-2-HAL, (Z)-3-hexen-1-ol = (Z)-3- HOL, (E)-2-hexenol = (E)-2-HOL, (Z)-3-hexen-1-yl acetate = (Z)-3-HAC], six common terpenes (β-pinene = β-PIN, β-myrcene = β-MYR, Z-ocimene = Z-OCI, linalool = LIN, benzyl acetate = BAC, β-caryophyllene = β-CAR), and indole = IND. We found that R. cerealis infested T. aestivum emitted the largest amounts of (Z)-3-HAL and (Z)-3-HAC, while T. aestivum infested by R. solani released the largest amount of LIN (7 or 11 days following stem infestation). VOCs released by the T. aestivum after R. cerealis (AGD I) and R. solani (AG 5) infestations were significantly larger in comparison to R. zeae (WAG-Z) and R. oryzae (WAG-O) for the volatiles (Z)-3-HAL, (E)-2-HAL, (Z)-3-HOL, (E)-2-HOL, (Z)-3-HAC, β-PIN, β-MYR, and LIN. With the exception of (E)-2-HOL, β-MYR, LIN, BAC, β-CAR, the other VOCs were emitted in similar amounts by infected T. aestivum 3 days following stem and soil inoculation. The quantities of induced VOCs were higher at days 7 and 11 than at 3 days post-infection, and greater when T. aestivum was infected with Rhizoctonia on the stem base than through the soil. Graphical abstract: Wheat infected by pathogens induced five common green leaf volatiles [GLVs; (Z)-3-hexenal, (E)-2-hexenal, (Z)-3-hexen-1-ol, (E)-2-hexenol, (Z)-3-hexen-1-yl acetate, six common terpenes (β-pinene, β-myrcene, Z-ocimene, linalool, benzyl acetate, β-caryophyllene), and indole. VOCs released by the plants after R. cerealis and R. solani infestation were significantly larger in comparison to R. zeae and R. oryzae, where the quantities of induced VOCs were higher at 7 days and 11 days than at 3 days post-infection, and greater when plants were infected with Rhizoctonia on the stem base than through the sil. Image 1 Highlights: Five common green leaf volatiles identified from wheat infected with pathogens. Higher volatile emissions found post-infection on days 7 and 11 than on day 3. Higher emissions found for Rhizoctonia infection on the stem base than in the soil. Higher emissions found for R. cerealis and R. solani than for R. zeae and R. oryzae .